2021
DOI: 10.5858/arpa.2021-0339-ra
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Diagnosis of Nonalcoholic Fatty Liver Disease

Abstract: Context.— Nonalcoholic fatty liver disease (NAFLD) encompasses steatosis and steatohepatitis. The cause may be multifactorial, and diagnosis requires correlation with clinical information and laboratory results. Objective.— To provide an overview of the status of histology diagnosis of steatosis, steatohepatitis, and associated conditions. Data Sources.— A li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…The new lifestyles derived from the lockdown have caused a statistically significant increase in obesity and overweight, which can be quantified with an increase in weight, BMI, percentage of fat mass, and abdominal perimeter as well as alterations in the lipid profile, simultaneously leading to a worsening of the obesity pandemic and an increase in metabolic pathologies [ 41 , 42 ] such as metabolic syndrome, insulin resistance in both the diabetic and non-diabetic individuals, and a greater risk of developing NAFLD [ 43 ], as seen in Table 2 and Table 3 , all of which affect the adult population worldwide [ 44 , 45 ], with metabolic syndrome representing the most frequent chronic liver disease in the United States [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The new lifestyles derived from the lockdown have caused a statistically significant increase in obesity and overweight, which can be quantified with an increase in weight, BMI, percentage of fat mass, and abdominal perimeter as well as alterations in the lipid profile, simultaneously leading to a worsening of the obesity pandemic and an increase in metabolic pathologies [ 41 , 42 ] such as metabolic syndrome, insulin resistance in both the diabetic and non-diabetic individuals, and a greater risk of developing NAFLD [ 43 ], as seen in Table 2 and Table 3 , all of which affect the adult population worldwide [ 44 , 45 ], with metabolic syndrome representing the most frequent chronic liver disease in the United States [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been several investigations of hepatic transporter alterations in CLD patients, resulting in the identification of dosing adjustments, there is nothing known regarding alterations of renal transporters in these patients (Droździk et al, 2020). The shortage of information is multifactorial, but the primary limitations include discrepancies in diagnosing CLD etiology, inaccuracy of kidney function assays to indicate renal biopsy evaluation, and invasiveness of biopsy procedures (Beben and Rifkin, 2015;Porrini et al, 2019;Younossi et al, 2019;Wieliczko et al, 2020;Lai et al, 2021). Combined, these limitations hinder clinical studies by restricting sample availability.…”
Section: Discussionmentioning
confidence: 99%
“…Liver biopsy has been used as the golden standard for the diagnosis of NASH [ 2 , 3 , 4 , 5 , 6 ]. Although some advanced imaging techniques, such as MRI, could be helpful for the diagnosis of NASH, our recent clinical trial showed that changes in hepatic fat content measured by MRI do not predict treatment-induced histological improvement of steatohepatitis [ 3 ].…”
Section: Histologic Diagnosis Of Nashmentioning
confidence: 99%
“…Although some advanced imaging techniques, such as MRI, could be helpful for the diagnosis of NASH, our recent clinical trial showed that changes in hepatic fat content measured by MRI do not predict treatment-induced histological improvement of steatohepatitis [ 3 ]. The histologic hallmarks of NASH are steatosis ( Figure 1 A), ballooned hepatocytes, and inflammation ( Figure 1 B) [ 2 , 7 ]. Steatosis is the simplest form of fatty liver disease characterized by the presence of fat droplets in hepatocytes without other abnormal findings.…”
Section: Histologic Diagnosis Of Nashmentioning
confidence: 99%
See 1 more Smart Citation